2017
DOI: 10.1007/s00148-017-0638-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender gaps in early educational achievement

Abstract: Educational achievement is often surprisingly gendered. After all, legislators, policymakers, and educators have worked for more than a generation to encode a principle of equal opportunity in education. Boys and girls generally attend the same schools, sit in classrooms alongside one another, and learn the same lessons. Why then do gender disparities in achievement persist? This question becomes all the more perplexing when one considers that it is not a simple matter of one gender having an overall edge in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 54 publications
3
22
0
1
Order By: Relevance
“…Here, two points deserve note. First, with regards to the UK dataset, the finding that EF performance varies significantly with SES for males but not females is consistent with the wider view that educational effects of social disadvantage might be especially marked in males (e.g., Cobb-Clark & Moschion, 2017;Ridge et al, 2017). However, the follow up analyses indicate that both males and females from the UK show indirect effect from SES to EF through general cognitive ability.…”
Section: Associations Between Ses and Ef Differ By Site And Gendersupporting
confidence: 75%
See 1 more Smart Citation
“…Here, two points deserve note. First, with regards to the UK dataset, the finding that EF performance varies significantly with SES for males but not females is consistent with the wider view that educational effects of social disadvantage might be especially marked in males (e.g., Cobb-Clark & Moschion, 2017;Ridge et al, 2017). However, the follow up analyses indicate that both males and females from the UK show indirect effect from SES to EF through general cognitive ability.…”
Section: Associations Between Ses and Ef Differ By Site And Gendersupporting
confidence: 75%
“…However, these differences did not carry over when looking at those with mathematical difficulties. However, in the UK at least, societal concerns about academic under-achievement in children from low-income families typically focus on males (e.g., Cobb-Clark & Moschion, 2017).…”
Section: Ses Executive Functions and Mathmentioning
confidence: 99%
“…Here, two points deserve note. First, with regards to the UK dataset, the finding that EF performance varies significantly with SES for males but not females is consistent SES EXECUTIVE FUNCTIONS AND MATH 31 with the wider view that educational effects of social disadvantage might be especially marked in males (e.g., Cobb-Clark & Moschion, 2017;Ridge et al, 2017). However, the follow up analyses indicate that both males and females from the UK show indirect effect from SES to EF through general cognitive ability.…”
Section: Associations Between Ses and Ef Differ By Site And Gendermentioning
confidence: 69%
“…Research has shown that gender differences in educational achievement emerge in the early years of school (Cobb‐Clark & Moschion, ) and can persist into adulthood (Anderson, ). There is also a growing body of evidence suggesting that social‐emotional skills observed in early childhood affect academic performance and labor market outcomes in later years (Cunha & Heckman, ; Cunha, Heckman, & Schennach, ).…”
Section: Introductionmentioning
confidence: 99%